TOTAL LOGAM Pb DAN Cr DALAM TANAH PERTANIAN DAN AIR DANAU BERATAN SERTA BIOAVAILABILITASNYA DALAM TANAH PERTANIAN DI DAERAH BEDUGUL - Saputra Jaya, I. G. Eka; Siaka, I Made; Diantariani, Ni Putu (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p05, 2014)
This paper discusses the total metal contents of Pb and Cr in soil of agricultural land and water of Lake Beratan, as well as their bioavailabilities in soil of the land in Bedugul area. This study aims to determine the total metals and the bioavailability of Pb and Cr in the soils of agricultural land in Bedugul area and determine the total metal Pb and Cr in the water of Lake Beratan. The total concentrations of Pb and Cr in soil samples and water of the lake were analyzed by using Atomic Absorption Spectrophotometer (AAS). The bioavailabilities of Pb and Cr in soil samples were also determined and analyzed by AAS. The results showed that the highest total concentrations of Pb and Cr were found in the soil located near the high way, which were 14.6162 mg/kg for Pb and 15.5380 mg/kg for Cr. The total concentration of  Pb and Cr in water of Beratan lake were 0.2802 mg/L and 0.2213 mg/L respectively. Cr metal was more bioavailable compared to Pb metal in the soil of Bedugul area. Bioavailable Pb was detected only in the soil sample collected from the area near the high way, which was about 45% bioavailable (as extracted by HCl) and potentially bioavailable was about 27% (the different percentages of Pb extracted by EDTA and by HCl. On the other hands, bioavailable Cr metal was detected in every soil sample (60-76%) and its potentially bioavailable ranged between 6 and 17%.
Keywords: Heavy metals, Pb, Cr, and bioavailability